The longest war : the enduring conflict between America and al-Qaeda - Bergen, Peter L., 1962- (New York : Free Press, 2011)
New York Times bestselling author Peter Bergen's definitive account of al Qaeda's evolution since 9/11 and the U.S. government's responses.
Holy Tuesday -- Explaining Bin Laden and 9/11 -- Blinking red -- Kicking ass -- The great escape -- The destruction of the base -- The gloves came off -- Home front: the first Bush term -- The war of error -- Almost losing the war the United States thought it had won -- Al-Qaeda 2.0 -- Al-Qaeda's quixotic quest for weapons of mass destruction -- United States of Jihad -- Pakistan: the new base -- The fall of al-Qaeda in Iraq and the rise of an Iraqi state -- The Jihad within -- The end of the "war on terror"? -- Obama's war -- The long hunt.
Includes bibliographical references (p. [437]-452) and index.
Keywords: Qaida (Organization); War on Terrorism, 2001-2009.; Terrorism -- United States -- Prevention; Terrorism -- Prevention; Iraq War, 2003-2011.